Over a million students use our free study notes to help them with their homework
First you need to make either the x value or the y value equal by multiplying each equation by a number.
2( 4x + 3y = 4 ) and 3( x + 2y = 2 ) which equals:
Equation 1: ( 8x + 6y = 8 ) and Eq...
15a2+ab-6b2 =(?a+?b)(?a-?b) Factors of 15= 3 and 5 Factors of 6= 2 and 3 If we try (3a+2b)(5a-3b) that gives us 15a2+10ab-9ab-6b2 = 15a2+ab-6b2 therefore the answer is (3a+2b)(5a-3b)
5(x+4)-3(2+3x)
Expand first bracket
5x+20-3(2+3x)
Expand second bracket
5x+20-6-9x
simplify
14-4x
This involves the product rule for counting. Step 1: Identify the possible numbers for the first digit 5, 6, 7, 8 or 9 (5 in total) Step 2: Identify the possible numbers for the second digit 2, 3, 5 or 7 ...
15a2+ab-6b2
=(?a+?b)(?a-?b)
factors of 15= 3 and 5
factors of 6= 2 and 3
if we try (3a+2b)(5a-3b) that gives us 15a2+10ab-9ab-6b2 Answered by Aayushi B. • Maths tutor2526 Views
←
591
592
593
594
595
→
Internet Safety
Payment Security
Cyber
Essentials